Pengaruh Penggunaan Teknologi Informasi Dan Keahlian Pemakai Terhadap Kualitas Informasi Akuntansi (Studi Empiris Pada Pemerintah Kabupaten Maluku Barat Daya) - Nicolaus Ahuluheluw; Cecilia Engko (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2020)
Research conducted with the title the influence of the use of information technology and user expertise on the quality of Accounting Information in Southwest Maluku District Government, The population in this study is all regional Apparatus Organizations (OPD) within the Government of Southwest Maluku Regency as many 37 OPD, while those used as information system operators (SIMDA) in each OPD as many 37 employees. The data collection technique used a questionnaire while the data analysis method used multiple regression analysisi techniques. Based on the results om empirical analysis, it is found that the use of information technology has a positive effect on the quality of accounting information. On the other hand, user expertise also has a positive effect on the quality of accounting information.